Evaluation of geomagnetic induced current on 275 kv power transformer for a reliable and sustainable power system operation in malaysia - Zawawi A.A.; Aziz N.F.A.; Kadir M.Z.A.A.; Hashim H.; Mohammed Z. (MDPI, 2023)
critical load; equipment; geomagnetic field; midlatitude environment; operations technology; sustainability; West Malaysia